Pengawasan Penyaluran Zakat, Infaq Dan Sedekah Untuk Pengentasan Kemiskinan Pada BAZNAS Kabupaten Sumbawa Tahun 2022-2023 - Maylandika, Oos; Sirin, Khaeron (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2025)
This study analyzes the mechanism and supervision system of zakat distribution by the National Zakat Agency (BAZNAS) of Sumbawa Regency, West Nusa Tenggara Province, in an effort to alleviate poverty during the 2022-2023 period. The results of the study indicate that BAZNAS Sumbawa Regency has collected zakat, infaq, and shadaqah (ZIS) funds of IDR 4.5 billion in 2023, which are distributed through five leading programs: Sumbawa Peduli, Sumbawa Sejahtera, Sumbawa Cerdas, Sumbawa Sehat, and Sumbawa Taqwa. Although there was a significant increase in fundraising compared to the previous report which recorded IDR 2.8 billion, the study identified several challenges in terms of community outreach, limited human resources, and optimization of distribution to the eight asnaf who are the targets of zakat. This study uses a descriptive qualitative approach with a case study design to analyze the mechanism and supervision of zakat distribution at BAZNAS Sumbawa Regency. This qualitative approach is based on the need to gain an in-depth understanding of the complexity of the zakat management process involving various social, economic, and institutional dimensions. Keywords: BAZNAS, Poverty, Supervision, Zakat.